Analysis of the Influence of Dental and Oral Health Services on BPJS Patient Satisfaction at Kaliwungu Kendal Health Center - Budhi Kismiaryani, Erna; Fauzan Azhmy, Muhammad; Pasaribu, Fajar (JMET: Journal of Management Entrepreneurship and Tourism, 2025)
The Kaliwungu Kendal Community Health Center provides comprehensive dental services with competent dental professionals. However, the service is still not optimal due to several patient complaints, such as waiting to see the dentist, waiting even after the dentist has arrived, not receiving immediate attention, a limited number of visits, etc. Creating quality services will undoubtedly lead to satisfaction among health service users. This study aims to determine the quality of service toward the satisfaction of BPJS patients at the Kaliwungu Kendal Community Health Center. The method used in this research is a quantitative analytical survey method with a cross-sectional study design. Data was collected with a sample size of 80 BPJS patients selected through sampling. The variables used in this study include the independent variable, service quality (X), and patient satisfaction (Y) as the dependent variable. The statistical analysis used in this study included a chi-square test and logistic regression. The results of the study show that all variables in the quality of dental and oral health service, including physical appearance, reliability, responsiveness, assurance, and empathy, have a positive and significant effect on patient satisfaction at the Dental Polyclinic of the Kaliwungu Kendal Community Health Center, with a p-value < 0.05. The tangible dimension has the most dominant effect, with a significant influence (exp(B)OR 18.259), followed by empathy (exp(B)OR 11.102), reliability (exp(B)OR 7.627), and assurance (exp(B)OR 5.091). However, responsiveness obtained the lowest satisfaction percentage compared to the other dimensions, with a value of (exp (B) OR 4.474).